THE EFFECT OF MOTORIZATION TO THE DEVELOPMENT OF URBAN PUBLIC TRANSPORT - Joewono, Tri Basuki; Santosa, Wimpy; Susilo, Yusak O.; Parikesit, Danang (Jurnal Transportasi, 2006)
AbstractÂ The aim of this study is to explore the effect of motorization to the development of urban public transportation in urban areas in Indonesian city in the last decade. The study employs many statistical data regarding motorization and urban public transport. It can be concluded that the motorization will continue to grow, and the existing transport policy should be re-questioned. It roots on the lack of acceptable provision of public transport in term of quality and quantity, but also as a result of high preference on using private transport. The challenge becomes excessive and complex, since there is no appropriate visionary road map for development of urban public transport. In answering this problem, the authors propose an abstract of two sequence approach, namely setting priority in taking side in provision of acceptable mobility for all, and followed with the redefinition of urban transport development by implementing transit-oriented development.Key words: motorization, urban public transport, development, sustainability.